Population pressure, political institutions, and protests: A multilevel analysis of protest events in African cities. (November 2022) - Dorward, Nick; Fox, Sean
Abstract: Why do some of Africa's urban areas experience higher rates of protest incidence than others? Numerous authors have highlighted the role of urbanisation and democratisation in determining cross-national variation in the rates of urban protest. Yet understanding has been hindered by failures to measure mechanisms at the appropriate spatial scale, analyse a sufficiently representative sample of urban centres, de-confound local and country-level factors, and consider what it is about specific urban centres that shapes variation in protest incidence. This paper presents new evidence on the determinants of protests in African urban centres by linking georeferenced data on urban settlements from the Urban Centres Database to the location of protest events taken from the Armed Conflict Location and Event Dataset. Fitting a series of multilevel regression models with cross-level effects, we simultaneously estimate variation in protest incidence as a function of local- and country-level factors and the interactions between them. Our results indicate that variation in protest incidence between urban centres can be explained by a combination of local-specific and country-level contextual factors including population size and growth, regime type, civil society capacity, and whether an urban centre is politically significant. These findings advance our understanding of how political and demographic factors interact and influence protest incidence in urban Africa.